Driving impact of delay in construction project / Muhammad Khairul Khusyairi Rusni and Syed Abdul Haris Syed Mustapa - Rusni, Muhammad Khairul Khusyairi; Syed Mustapa, Syed Abdul Haris (2023)
This thesis examines the factors contributing to delays in construction projects and their impacts on project outcomes. Construction projects often face challenges and delays that significantly impact project schedules, costs, and client satisfaction. Understanding these factors and their consequences is crucial for successfully managing and completing construction projects. The study employs a comprehensive research methodology, including literature reviews, data collection, and analysis of real-world construction projects. The data collected encompass various project types, sizes, and geographical locations to ensure a broad industry representation. The findings reveal several key factors that contribute to delays in construction projects. The findings and recommendations outlined in this thesis offer valuable insights for practitioners, policymakers, and researchers and drive positive changes in project management practices.